INSTRUMEN SUPERVISI DALAM IMPLEMENTASI KURIKULUM MERDEKA (IKM) PADA JENJANG SEKOLAH DASAR - Yusniarti Yusniarti; Mila Yulia Herosian (LPPM Institut Pendidikan Nusantara Global, 2023)
The Merdeka Curriculum is a part of the Ministry of Education and Culture's efforts to address long-standing learning problems, exacerbated by the Covid-19 epidemic. Low student learning outcomes, especially in basic areas such as reading literacy, define this problem. Teachers and principals are important components in the successful implementation of teaching and learning activities. Therefore, a teacher must really understand the curriculum, starting from a theoretical understanding to its application in the classroom, which is always under the supervision of the principal. The purpose of this study was to determine the supervision tools used in the implementation of the education unit level curriculum (KTSP) at the elementary school level in Padang Panjang City, West Sumatra. The data collection procedures used in this study are: (1) in-depth interviews, (2) participant observation, and (3) documentation study. The findings of this study include nine techniques used by principals in the supervision process during the implementation of the independent curriculum (KKM) at the primary school level using the instruments used, namely. (1) review of learning administration; (2) review of the flow of learning objectives; (3) review of learning modules; and (4) evaluation of learning implementation every school year